Aplikacije računalniških algoritmov - Žalik, Borut (University of Maribor Press, 2023)
Applications of Computer Algorithms. Textbook Applications of Computer Algorithms is dedicated to the BSc students of Computer Science with the aim of get familiar with the algorithms, used almost everyday by the users. By implementing those algorithms the students shell obtain the necessary routine to enter into the art of programing of the universal machine, i.e. computer. The textbook contains the following chapters: sorting in linear time, pattern matching in strings, minimum editing distance, basic cryptographic algorithms, lossless data compression, string transformations, prefix arrays and prefix trees, and algorithms in raster space (chain codes and space filling curves).